DESIGN OF 28 GHZ MICROSTRIP MIMO ANTENNAS FOR FUTURE 5G APPLICATIONS - Yusnita Rahayu; Luthfi Afif; Muhammad Rizki Radhelan; I. Yasri; Feri Candra (Universitas Mercu Buana, 2018)
The 5G system requires more significant system capacity, more full bandwidth, and higher frequency. One type of antenna that can be used to increase the channel capacity is microstrip MIMO antenna. The Federal Communications Commission of the U.S. has recently designated the frequency band from 27.5 to 28.35 GHz for 5G applications. In this paper, the design of 28 GHz microstrip MIMO antenna for future 5G applications was proposed. The antenna was designed by using RT Duroid 5880 substrate with a dielectric constant of 2.2 and the loss tangent of 0.0009. The antenna operated from 27.10 GHz to 28.88 GHz with 1.78 GHz (6.35%) of bandwidth. The antenna consisted of four elements feeding by a microstrip line. Based on the simulated results, the high gain of 14.8 dBi is obtained with a linear directional pattern. Comparison performance regarding gain, return loss, VSWR and bandwidth are also presented for single, two and four elements. It is shown that the increasing number of elements of antenna increased the gain and the return loss. The antenna meets the 5G requirements.